Energy tax and regulatory policy in Europe reform priorities - Parry, Ian W. H. 1965-; Pittel, Karen 1969-; Vollebergh, Herman R. J. 1961- (MIT Press, 2017)
Concise introductions to the main issues in energy policy and their interaction with environmental policies in the EU.
Keywords: Europäische Union; Energy policy-Europe; Energy tax-Europe; Politische Reform; Energiesteuer; Energiewende; Umweltzertifikathandel; Elektrizitätsmarkt; Aufsatzsammlung